Examination of Extended Techniques on Double Bass in Terms of Performance Practices - H. Özgür Akkor; Koray Sazlı (Konservatoryum)
When examining the double bass repertoire from the second half of the twentieth century to the present day, it becomes clear that, similar to other instruments, extended performance techniques are frequently used to achieve different timbres on the double bass, and the number of works incorporating these techniques has increased. The interactive relationship between composers and performers has significantly enriched the instrument’s repertoire, leading to the introduction of many new playing techniques in performance practices. There has been a move beyond standard notation, with the emergence of different notational systems that express new techniques. This use varies from composer to composer. Contemporary composers strive to use the expressive possibilities of instruments to their fullest, and by leveraging modern technological advancements, they seek to create different timbres and compositions. Sometimes, they develop these techniques themselves. This study explains what extended performance techniques on the double bass are, how they are classified, and how they are applied in performance practices. Examples of their use in contemporary solo double bass works are provided. The evaluations and data obtained regarding extended performance techniques and their reflections in composition are presented through descriptive qualitative research methods. The goal is to provide information about extended performance techniques on the double bass within contemporary music, including the repertoire that incorporates these techniques, notation, and performance practices.